Benefits of Foot Exercises in Increasing Muscle Strength Diabetes Mellitus Patients At Grandmed Lubuk Pakam Hospital In 2023 - Simarmata, Juni Mariati; Syatriawati, Syatriawati; Handayani, Dwi (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LP2M) Institut Kesehatan Medistra Lubuk Pakam, 2023)
Diabetes mellitus (DM) is a type of disease that is generally known in society as diabetes. This disease can occur due to an increase in blood sugar levels so that insulin secretion experiences a progressive decrease. Complications of musculoskeletal disorders are one type of DM complication that causes weakness in the leg muscles. Foot exercises are one of the therapies that diabetes mellitus patients can do to overcome foot muscle problems. This foot exercise aims to increase blood circulation so that it can strengthen the leg muscles. If blood circulation is good, nutrition will flow more smoothly to body tissues so that muscle movement is not disturbed. Service activities are carried out through socialization and demonstrations using lectures, discussions and questions and answers. The number of PkM participants who were DM patients was 20 people who were determined using the total sampling method. PkM activities use a pre-test and post-test system with written questions to measure the benefits and increase in knowledge obtained by PkM participants. The results of the service showed that PkM activities through providing foot exercises to DM patients were beneficial in increasing the leg muscle strength of DM patients, where there was an average increase of 1.15 and a p value of 0.000. Apart from that, the level of knowledge of PkM participants regarding foot exercise material for DM patients also experienced an increase in knowledge by 90% or as many as (18 PkM participants) understood the PkM material well.